Implementasi Kebijakan Program Indonesia Pintar (PIP) di Wilayah Kementerian Agama Kabupaten Sidoarjo - Lilik Fadzlun; Zaidatun Ni’mah; Lindah Ayu Lestari; Lilik Huriyah; Abdul Rahman (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
This study aims to identify and describe the implementation of the Smart Indonesia Program Policy or Program Indonesia Pintar (PIP) in the area of ??the Ministry of Religion, Sidoarjo Regency. The research method used is qualitative research. Data collection techniques used interviews, observation, and documentation with informants, namely application managers to verify the Smart Indonesia Program. Data analysis techniques are data reduction, data presentation and conclusions. The results showed that the Program Indonesia Pintar (PIP) carried out at the Ministry of Religion Office of Sidoarjo Regency was running well so that it could verify student data data to get financial assistance. Students who have registered at educational institutions with KIP, KKS, PKH, as well as parents who have been laid off. This program aims to help parents who are vulnerable to poverty in order to get a good education and prevent dropouts. Every year the funds are disbursed in registered student accounts.